2014
DOI: 10.3389/fnbeh.2014.00126
|View full text |Cite
|
Sign up to set email alerts
|

Distinct phenotypes of new transmembrane-domain neuregulin 1 mutant mice and the rescue effects of valproate on the observed schizophrenia-related cognitive deficits

Abstract: Accumulating evidence suggests that neuregulin 1 (NRG1) might be involved in the neurodevelopment, neural plasticity, GABAergic neurotransmission, and pathogenesis of schizophrenia. NRG1 is abundantly expressed in the hippocampus, and emerging studies have begun to reveal the link between NRG1 signaling and cognitive deficits in schizophrenic patients. Because the transmembrane domain of NRG1 is vital for both forward and reverse signaling cascades, new Nrg1-deficient mice that carry a truncation of the transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 98 publications
5
25
0
Order By: Relevance
“…Guidotti et al 2000;Hashimoto et al 2003) and other transcriptional markers of GABA, such as mRNA expression of the 1, 5 and  subunits of the GABA A receptor in the brain of patients with schizophrenia. In agreement with this human postmortem finding, a study by (Pei et al 2014) found abnormally low levels of GAD67 in male, but not female, type I Nrg1 "knockout" mice in the hippocampus, and another study by (Yin et al 2013) observed elevated 1 in type I Nrg1 overexpressing mice relative to wild type mice in frontal cortex and hippocampus. In light of the human postmortem findings, it may be that Nrg1 leads to small and often undetectable changes in GAD67 and other markers of GABAergic activity through its selective more potent effects on PV+ interneurons, but it is only when combined with the effects of several other risk genes and environmental stressors in patients with schizophrenia, that broader aberrations in GABA occur.…”
Section: Nrg1 and Inhibitory Neurotransmissionsupporting
confidence: 61%
See 1 more Smart Citation
“…Guidotti et al 2000;Hashimoto et al 2003) and other transcriptional markers of GABA, such as mRNA expression of the 1, 5 and  subunits of the GABA A receptor in the brain of patients with schizophrenia. In agreement with this human postmortem finding, a study by (Pei et al 2014) found abnormally low levels of GAD67 in male, but not female, type I Nrg1 "knockout" mice in the hippocampus, and another study by (Yin et al 2013) observed elevated 1 in type I Nrg1 overexpressing mice relative to wild type mice in frontal cortex and hippocampus. In light of the human postmortem findings, it may be that Nrg1 leads to small and often undetectable changes in GAD67 and other markers of GABAergic activity through its selective more potent effects on PV+ interneurons, but it is only when combined with the effects of several other risk genes and environmental stressors in patients with schizophrenia, that broader aberrations in GABA occur.…”
Section: Nrg1 and Inhibitory Neurotransmissionsupporting
confidence: 61%
“…For example, levels of parvalbumin are elevated in the frontal cortex in type I Nrg1 overexpressing mice compared to wild type mice . In contrast, the TM Nrg1 model is associated with reduced parvalbumin in the hippocampus for male, but not female, mice (Pei et al 2014). Also, genetic ablation of the Nrg1 receptor tyrosine kinase, ErbB4, down-regulates the number of PV + interneurons in the same brain region by 30% from normal levels (Fisahn et al 2009).…”
Section: Nrg1 and Inhibitory Neurotransmissionmentioning
confidence: 87%
“…Male-specific deficits in object recognition were confirmed by Pei et al, however this group found that cue-dependent fear conditioning was also impaired in males but not females (Pei et al 2014). Furthermore, male but not female TM-Nrg1 +/-show reduced hippocampal protein expression of the GABA synthesizing enzyme GAD67 and the fast-spiking GABAergic interneuron marker, parvalbumin (Pei et al 2014). These fastspiking interneurons are thought to be critically involved in the regulation of cognitive function (Uhlhaas 2013).…”
Section: Genetic Models Of High-risk Genesmentioning
confidence: 75%
“…Neonatal, peripheral administration of NRG1 type 1 protein in mice has also been shown to produce adult deficits in sensorimotor gating and learned inattention tasks, and these were reversed by antipsychotic treatment during adulthood (Kato et al, ). A novel line of transmembrane‐domain partial Nrg1 deletion showed a sex‐specific (males only) deficit in object recognition memory, as well as in both contextual and cued fear learning (Pei et al, ); these cognitive deficits were reversed by chronic treatment with valproate, a mood stabilizer and anticonvulsant with actions that include potentiation of GABAergic function.…”
Section: Mutant Models Of Candidate Risk Genes For Schizophreniamentioning
confidence: 99%